2014
DOI: 10.1080/14786419.2014.940588
|View full text |Cite
|
Sign up to set email alerts
|

Effects of UV-B radiation on total phenolic, flavonoid and hypericin contents inHypericum retusumAucher grown underin vitroconditions

Abstract: This study was conducted to increase total phenolics, flavonoids and hypericin accumulation in in vitro cultures of Hypericum retusum Aucher to determine the appropriate time of UV radiations. Proliferation of plantlets on Murashige-Skoog medium containing 0.5 mg L(- 1)N-6-benzylaminopurine was achieved under in vitro conditions. Then, the plantlets were exposed to UV-B radiation for different periods (15, 30, 45 and 60 min). The highest total phenolics, flavonoids and hypericin accumulation (43.17 ± 0.8; 35.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…In our study, UV‐B stress dramatically changed the related enzyme activities and caused significant accumulation of vitamin C, phenolics and flavonoids in mung bean sprouts. Our results are in agreement with those of the previous studies, which reported that UV‐B stress can increase the content of vitamin C, phenolics and flavonoids in buckwheat sprouts (Tsurunaga et al ., ), fruit of the tomato (Castagna et al ., ), wheat (Agrawal & Rathore, ) and hypericum (Namli et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In our study, UV‐B stress dramatically changed the related enzyme activities and caused significant accumulation of vitamin C, phenolics and flavonoids in mung bean sprouts. Our results are in agreement with those of the previous studies, which reported that UV‐B stress can increase the content of vitamin C, phenolics and flavonoids in buckwheat sprouts (Tsurunaga et al ., ), fruit of the tomato (Castagna et al ., ), wheat (Agrawal & Rathore, ) and hypericum (Namli et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The biosynthesis of flavonoid and the expression levels of related genes are regulated by phytochrome, cryptochrome, phototropin, and UV-B photoreceptors [43,44]. For example, flavonoid biosynthesis was suppressed by increasing the amount of far-red light of phytochrom [45], whereas UV-A / blue light induction of the flavonoids biosynthesis was mediated principally by cryptochrome [44], in addition, the biosynthesis of flavonoids and the expression levels of related genes are induced most effectively by UV-B light [46,47]. In fact, a white light source that contains all these wavelengths is usually used to induce flavonoid biosynthesis.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, Agati et al ( 2013 ) concluded that UV-B photoprotection is just one of the essential functions of fl avonoids which have several other myriad roles in plant growth regulation. Namli et al ( 2014 ) observed an increase in the total fl avonoids, phenolics , and hypericin content in the in vitro cultures of Hypericum retusum var. During such stress, there is a burst in reactive oxygen species (ROS) production, resulting in various damages which we have discussed before.…”
Section: Flavonoidsmentioning
confidence: 87%
“…However, the most important functions of fl avonoids arise when the plants face UV-B stress. When the cultured plantlets were exposed to UV-B rays for 15, 30, 45, and 60 min, the highest total phenolics, fl avonoids, and hypericin accumulation (43.17 ± 0.8; 35.09 ± 0.8; 2.7 ± 0.05 mg g −1 , respectively) was achieved at 45 min of UV-B exposure, whereas the contents of these metabolites in the naturally grown plants were 23.33 ± 0.9, 18.62 ± 0.3, and 1.6 ± 0.01 mg g −1 respectively (Namli et al 2014 ). Koyama et al ( 2012 ) reported a decrease in the fl avonol content in the skin of grape berries (under UV shield).…”
Section: Flavonoidsmentioning
confidence: 98%